The Effectiveness of Goes to School Police in Increasing Student Traffic Awareness in Order to Reduce Police Accidents in the Ngawi Police Jurisdiction Area - Pinaya,FitrahRamadhan (Indonesian Journal of Police Studies, 2024)
The National Police is a public service institution that maintains security, enforces the law and serves the community in accordance with Law Number 2 of 2002. The Police Goes to School program aims to provide students with an understanding of traffic rules, encourage their discipline and awareness in traffic for safety and develop cooperation. The aim of this writing is to describe and analyze the factors that can influence the implementation of the "Police Goes to School" program carried out by the South Kalimantan Unit at the Ngawi Police Traffic Unit to examine the inhibiting factors in its implementation. The method used is a qualitative method by describing the overall natural conditions regarding the effectiveness of Police Goes to School in increasing students’ traffic awareness in order to reduce traffic accidents in the Ngawi Police jurisdiction in the form of words and language regarding the objects studied. The results obtained in this writing are that the implementation of Police Goes to School in an effort to reduce traffic accidents by the Ngawi Police Traffic Security Unit is still not effective because it is influenced by several factors, namely the lack of planning, supporting facilities and the ability to liven up the atmosphere. The Ngawi Police Traffic Unit in reducing traffic accidents involving students is increasing awareness among students about traffic rules to maintain safety when driving.